Reinfection of the mouse genital tract with Chlamydia trachomatis: the relationship of antibody to immunity. - Tuffrey, M. (1984)
Progesterone-treated CBA mice which had had genital infections with a fast, human strain of Chlamydia trachomatis either 8, 16, 58, or 69 weeks previously were rechallenged through the uterine wall, along with groups of untreated controls. Serum IgG antibody and/or local IgA antibody was measured using a micro-immunofluorescence technique. Although the infection was self-limiting, chlamydiae were cleared significantly more quickly from the previously infected groups than from their controls in all experiments. However, mice which had had a previous infection recently and which had high titres (geometric mean 1: greater than or equal to 2048) of serum IgG antibody and local IgA antibody immediately before rechallenge, were as susceptible as mice which had had a distant past infection and which had much lower titres (geometric mean 1:48) of serum IgG antibody. Thus, some immunity was induced in the mouse model, but pre-existing antibody seemed to be of little importance in this, and did not influence the initial susceptibility to reinfection.